2011
DOI: 10.1128/jvi.00810-11
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adenoviruses in Wild Primates: a High Level of Genetic Diversity and Evidence of Zoonotic Transmissions

Abstract: Adenoviruses (AdVs) broadly infect vertebrate hosts, including a variety of nonhuman primates (NHPs).In the present study, we identified AdVs in NHPs living in their natural habitats, and through the combination of phylogenetic analyses and information on the habitats and epidemiological settings, we detected possible horizontal transmission events between NHPs and humans. Wild NHPs were analyzed with a pan-primate AdV-specific PCR using a degenerate nested primer set that targets the highly conserved adenovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
100
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 56 publications
17
100
1
1
Order By: Relevance
“…Frequent natural HAdV recombination emerging from virus transmission between great apes and humans will increase genetic AdV diversity and thus the likelihood that pathogenic variants will appear (Robinson et al, 2013a;Walsh et al, 2009). The likelihood for infection with such recombinant AdVs increases for people in some regions of sub-Saharan Africa, because of the high AdV prevalence in NHPs (Hoppe et al, 2015;Roy et al, 2009;Wevers et al, 2011), overlapping habitats of humans and great apes, and bush meat hunting and trade (Parrish et al, 2008;Woolhouse & Gaunt, 2007). Since some AdVs have a zoonotic potential, causing respiratory outbreaks both in humans and monkeys (Chen et al, 2011;Chiu et al, 2013;Kandel et al, 2010;Sanchez et al, 2001), further investigations on primate AdVs in sub-Saharan disease outbreaks are needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent natural HAdV recombination emerging from virus transmission between great apes and humans will increase genetic AdV diversity and thus the likelihood that pathogenic variants will appear (Robinson et al, 2013a;Walsh et al, 2009). The likelihood for infection with such recombinant AdVs increases for people in some regions of sub-Saharan Africa, because of the high AdV prevalence in NHPs (Hoppe et al, 2015;Roy et al, 2009;Wevers et al, 2011), overlapping habitats of humans and great apes, and bush meat hunting and trade (Parrish et al, 2008;Woolhouse & Gaunt, 2007). Since some AdVs have a zoonotic potential, causing respiratory outbreaks both in humans and monkeys (Chen et al, 2011;Chiu et al, 2013;Kandel et al, 2010;Sanchez et al, 2001), further investigations on primate AdVs in sub-Saharan disease outbreaks are needed.…”
Section: Resultsmentioning
confidence: 99%
“…AdVs attributable to nearly all HAdV species have been detected in wild and captive African great apes and are shed with faeces in high numbers (Duncan et al, 2013;Hoppe et al, 2015;Roy et al, 2009;Seimon et al, 2015;Wevers et al, 2010Wevers et al, , 2011. In captive NHPs, AdVs are associated with respiratory disease (Chen et al, 2011;Chiu et al, 2013;Wevers et al, 2010), but almost nothing is known about the clinical relevance of AdVs in wild NHP populations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, HAdV-D67 was identified as a recombinant between HAdV-D9, -D25, -D26, -D33, and -D46 (46,55). Recent data provide evidence for the occurrence of recombination between different HAdV species, and even between HAdVs and SAdVs (56,57). Computational analysis of HAdV-E4, the only representative of species E, indicated that this virus is of zoonotic origin and evolved through two interspecies recombination events with lateral partial gene transfer.…”
Section: Current Status Of Hadv Types and Evolution Of Human Adenovirmentioning
confidence: 99%
“…New HAdV types have since been identifi ed by several authors based on genomic data, including several emerging and recombinant viruses [7][8][9][10][11][12][13][14]. Most recently, a primate adenovirus from New World monkeys was detected which crossed the species barrier to infect humans [15,16]. The majority of new HAdV types are homologous recombination within the same subgenus, and as a result, certain new serotypes acquire different pathogenicities.…”
Section: Introductionmentioning
confidence: 99%